Análisis de la demanda de transporte no motorizado en estudiantes universitarios: caso Universidad de la Costa (2015)
Studies of transport demand are tools currently used to identify and characterize the choice of a way of transporting a given population or sample. First the population identifies itself to study, then a field study is done, then we characterize the social sphere (sex, income, place of residence, place of employment, reason for travel, etc.). and finally statistical data with their preferred modes are determined. In this work we study degree modes of transport used by students and / or employees of the University of the Coast. On the regional and local context of the city, transport modes to study are: bus (includes Transmetro and traditional) car, motorcycle, taxi, walk and as an aggregate study analyzed bicycle. The study of transport demand was made 240 people, of which 60.34% are male and 39.66% female. People ages ranging from 16 to 40 years. The 93.22% live in the city and 7.78% moves from out of town. The mode of transport is the most widely used bus with 82.40% followed by taxi to 9.60%, the car has a share of 5.20%, 1.60% hike one and finally with 1. 20% the bike. After a stated preference survey, ie, simulation of situations of choice, we proceeded to make a prediction models mode of transport, with the existing theory and based on previous studies for the veracity of the study. These models are then compared to what the person chosen and the percentage of assertiveness model was quantified.